Subcapsular hepatic hematoma in HELLP syndrome in a Lima reference hospital - Gonzales Carrillo, Oswaldo M. (2017)
Objective: To determine the clinical characteristics and management of subcapsular hepatic hematoma (SHH) as a result of severe preeclampsia and HELLP syndrome in the period 2004-2016. Design: Descriptive, retrospective study, series of cases type. Setting: Instituto Nacional Materno Perinatal, Lima, Peru. Material: We reviewed the clinical charts of patients with SHH. Methods: The clinical charts of cases with SHH attended at our institution between 2004 and 2016 were reviewed. Search also included PubMed and the results were compared with those in the literature. Main outcome measures: Incidence, clinical features, diagnosis, management and results. Results: 31 cases of SHH were found, with an incidence of 1 in 6 000 to 9 000 births. The mean maternal age was 34 years and 80% were multiparous. Diagnosis was usually through direct visualization of the hepatic rupture during caesarean section (45%). The most frequent symptoms were upper abdominal pain (52%), headache (36%), alteration of consciousness (31%) and hematuria (48%). Liver packing was performed in 90% of the cases; observation and monitoring, in 10%. In 44% of cases, a Bogotá bag was placed during the first surgery. During the last 2 years, we have recurred to vacuum-assisted closure to prevent compartment syndrome. 74% of cases survived and 26% died. The average hospital stay was 23.2 days. Conclusions: The incidence of subcapsular hepatic hematoma as a result of severe preeclampsia and HELLP syndrome was 1 in 6 000 to 9 000 births. Hematuria was a significant sign and should be studied further. Liver packing was performed in 90% of patients, a statistically significant higher rate than that reported in the literature (p=0.0025), maybe due to a preference for conservative management. Despite only performing surgical treatment, the mortality rate was similar to that reported in the literature (26% versus 17%; p=0.2702).